Intestinal Immune System and Amplification of Mouse Mammary Tumor Virus - Chen, Lankai; Zhang, Xipeng; Liu, Guisheng; Chen, Shuo; Zheng, Minying; Zhu, Siwei; Zhang, Shiwu (Frontiers in Cellular and Infection Microbiology, 2022)
Mouse mammary tumor virus (MMTV) is a virus that induces breast cancer in mice. During lactation, MMTV can transmit from mother to offspring through milk, and Peyer’s patches (PPs) in mouse intestine are the first and specific target organ. MMTV can be transported into PPs by microfold cells and then activate antigen-presenting cells (APCs) by directly binding with Toll-like receptors (TLRs) whereas infect them through mouse transferrin receptor 1 (mTfR1). After being endocytosed, MMTV is reversely transcribed and the cDNA inserts into the host genome. Superantigen (SAg) expressed by provirus is presented by APCs to cognate CD4+ T cells via MHCII molecules to induce SAg response, which leads to substantial proliferation and recruitment of related immune cells. Both APCs and T cells can be infected by MMTV and these extensively proliferated lymphocytes and recruited dendritic cells act as hotbeds for viral replication and amplification. In this case, intestinal lymphatic tissues can actually become the source of infection for the transmission of MMTV in vivo, which results in mammary gland infection by MMTV and eventually lead to the occurrence of breast cancer.